Genotype-relevant neuroimaging features in low-grade epilepsy-associated tumors - Iijima, Keiya; Fujii, Hiroyuki; Suzuki, Fumio; Murayama, Kumiko; Goto, Yu-ichi; Saito, Yuko; Sano, Terunori; Suzuki, Hiroyoshi; Miyata, Hajime; Kimura, Yukio; Nakashima, Takuma; Suzuki, Hiromichi; et al. (Frontiers in Neurology, 2024)
Introduction Low-grade epilepsy-associated tumors are the second most common histopathological diagnoses in cases of drug-resistant focal epilepsy. However, the connection between neuroimaging features and genetic alterations in these tumors is unclear, prompting an investigation into genotype-relevant neuroimaging characteristics. Methods This study retrospectively analyzed neuroimaging and surgical specimens from 46 epilepsy patients with low-grade epilepsy-associated neuroepithelial tumors that had genetic mutations identified through panel sequencing to investigate their relationship to genotypes. Results Three distinct neuroimaging groups were established: Group 1 had indistinct borders and iso T1-weighted and slightly high or high T2-weighted signal intensities without a diffuse mass effect, associated with 93.8% sensitivity and 100% specificity to BRAF V600E mutations; Group 2 exhibited sharp borders and very or slightly low T1-weighted and very high T2-weighted signal intensities with a diffuse mass effect and 100% sensitivity and specificity for FGFR1 mutations; and Group 3 displayed various characteristics. Histopathological diagnoses including diffuse low-grade glioma and ganglioglioma showed no clear association with genotypes. Notably, postoperative seizure-free rates were higher in Group 1 tumors (BRAF V600E) than in Group 2 tumors (FGFR1). Discussion These findings suggest that tumor genotype may be predicted by neuroimaging before surgery, providing insights for personalized treatment approaches.